EFEKTIVITAS PENGELOLAAN DANA DESA DI DESA KOLOR, KECAMATAN KOTA SUMENEP, KABUPATEN SUMENEP - Abdul Gafur Rinaldi; A Iedar Zulfikar FQ (PT. Samudra Solusi Profesional, 2024)
This research aims to evaluate the extent to which village fund management is effective in Kolor Village, Sumenep City District, Sumenep Regency. The research method used is descriptive qualitative with a case study approach, and the data source used comes from the Village Fund Budget Realization Report. The findings from this research indicate that Village Fund Allocation Management has been effective in accelerating the development process in Kolor Village, Sumenep City District, and Sumenep Regency. In addition, obstacles were identified in the form of a lack of understanding and participation of human resources in managing village fund allocations.